FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERUBAHAN EKG PADA PASIEN HIPERTENSI - TRESNA ADI PRAYOGA; AHMAD HANDAYANI (JURNAL ILMIAH SIMANTEK, 2022)
Hypertension is one of the main problems of mortality and morbidity in cardiovascular disease in Indonesia, prolonged hypertension can cause complications in the heart in the form of left ventricular hypertrophy, to detect left ventricular hypertrophy requires the use of an easy and inexpensive tool, namely electrocardiography. The purpose of this study is to look at some of the factors causing the electrocardiographic picture that may have an effect on the occurrence of left ventricular hypertrophy including age, gender, length of time suffering from hypertension, obesity and diabetes mellitus. The design of this study was retrospective descriptive with a cross-sectional approach. The research subjects were 42 hypertensive heart disease (HHD) patients who had conducted an electrocardiography examination at Mitra Medika Bandar Klippa General Hospital for the period January 2019 - July 2020 who met the inclusion and exclusion criteria. This result of this research there is an effect of a long history of suffering from hypertension with left ventricular hypertrophy with a value (p = 0.006).